Forensic Thermal Analysis: Topic, Object, Tasks, Main Research Directions - Bohdaniuk, Ihor (Теорія та практика судової експертизи і криміналістики, 2023)
Formation procedure of thermal engineering researches as a separate species of forensic engineering based on principles of genesis in forensic science is considered. The latest research in the field of specific expertise use during production, distribution, transmission and consumption of energy resources is analyzed. A review of the results performed at National Scientific Center «Hon. Prof. M. S. Bokarius Forensic Science Institute» multidisciplinary forensic researches on violations of accounting and theft of natural gas by interfering with operation of accounting devices, on determining the scope of performed works on installation, testing and operation of heating equipment. Purpose: formulate definition of the concepts of the topic and object of the forensic thermal analysis; compile a list of areas of forensic thermal research and form typical tasks for this type of forensic science based on. In order to achieve the goal, the methods of scientific cognition are applied: observation, comparison, abstraction, analysis, synthesis, modeling, etc. Abbreviated and expanded definition of topic of forensic thermal analysis is proposed. On the basis of general structure of the tasks of forensic engineering a, as well as the results of the analysis of the requests of the pre-trial investigation bodies and the court regarding the conduct of forensic examinations in the thermal direction, a general list of tasks of the forensic heat engineering examination with structuring into four groups was developed. A list of the main areas of research in forensic thermal analysis has been compiled.